Adult aggressive behavior in humans and biomarkers: a focus on lipids and methylation - Fiona A. Hagenbeek; Jenny van Dongen; Cornelis Kluft; Thomas Hankemeier; Lannie Ligthart; Gonneke Willemsen; Eco J.C. de Geus; Jacqueline M. Vink; Meike Bartels; Dorret I. Boomsma (Hygeia Press di Corridori Marinella, 2018)
Aggression shows large variation between individuals, with about 50% explained by genetic factors. Biomarkers related to aggression have been reported for lipid metabolism and for epigenetic marks. Methylation and blood lipid levels are not independent and differential methylation can be a consequence of variation in blood lipid levels. We hypothesized that the methylation level of such loci in blood can inform us if aggression is associated with long-term exposure to lipid levels. If this is the case, we expect to find that loci where methylation levels are influenced by lipid levels to show differential methylation in aggressive individuals. Such loci might complement classic lipid level measures as a biomarker for lipid-related disturbances in aggression. As a first step, we examined the association of lipid levels and related biomarkers with aggression in a large adult population cohort (N = 5,588) and in 31 monozygotic (MZ) twin pairs who were discordant for aggression, as well as 12 extremely discordant MZ pairs. Biomarkers were not significantly associated with aggression in the population cohort. In the discordant MZ pairs we identified significant within-pair differences for glucose and marginally significant differences for lipids and cytokines, with the more aggressive twin showing lower levels of glucose and low density lipoprotein cholesterol and higher levels of fibrinogen, C-reactive protein and interleukin-6. The analysis of epigenetic data in the MZ pairs discordant for aggression did not show enrichment for lipid cytosine guanine dinucleotides (CpGs) and we observed no enrichment of lipid CpGs in an epigenome-wide association study of aggression in the population cohort. These results did not support the hypothesis that lipid CpGs show differential methylation in adult aggression. A next step will be to examine the role of biomarkers in aggression across the lifespan, including childhood, and to explore a more holistic biomarker approach, such as offered by metabolomics.